Case Report: Delayed Onset Multi-Organ Toxicities in a Melanoma Patient Achieving Complete Response to BRAF/MEK Inhibition - Knochelmann, Hannah M.; Ware, Michael Brandon; Rali, Aditya; Linderman, Susanne; Shantha, Jessica G.; Lawson, David H.; Yushak, Melinda; Swerlick, Robert; Paulos, Chrystal M.; Yeh, Steven; Kudchadkar, Ragini (Frontiers in Oncology, 2022)
Autoimmune toxicities, while common following treatment with cancer immunotherapies, are not well-characterized in patients treated with BRAF/MEK inhibitors. Emerging data suggest that autoimmune effects may be linked with superior responses to both treatment modalities; however, there is little evidence describing mechanisms of immune-related toxicity for patients on BRAF/MEK inhibitors. Here we describe the experience of a 59-year-old HLA-A2, A29, B27-positive male patient with recurrent/metastatic melanoma. After progression on checkpoint inhibitor therapy, he was treated with dabrafenib/trametinib followed by encorafenib/binimetinib, which were well-tolerated. 18 months into BRAF/MEK inhibitor therapy, he developed a series of sudden-onset, severe toxicities including bilateral panuveitis, cytopenias, joint pain, skin rash, hypercalcemia and interstitial nephritis, which led to BRAF/MEKi cessation. At that time, the patient was found to have a complete response, which is ongoing at the time of this publication despite withdrawal of BRAF/MEKi therapy over one year ago. Immunological analyses revealed induction of a peripheral type-17 cytokine signature characterized by high IL-23, IL-6, IL-10, IL-17A/F, IL-1b and IL-21 among other cytokines in plasma corresponding with the height of symptoms. These findings highlight a novel instance of delayed autoimmune-like reaction to BRAF/MEK inhibition, and identify a possible role for Th/Tc17 activation in their pathogenesis thus warranting future clinical and immunological characterization.